2015
DOI: 10.18632/oncotarget.5601
|View full text |Cite
|
Sign up to set email alerts
|

Induction of USP17 by combining BET and HDAC inhibitors in breast cancer cells

Abstract: Members of the bromodomain and extra-C terminal (BET) domain protein family and the histone deacetylase (HDAC) enzyme family regulate the expression of important oncogenes and tumor suppressor genes. Here we show that the BET inhibitor JQ1 inhibits proliferation and induces apoptosis of both triple negative and estrogen receptor positive breast cancer cells. Consistent with the critical role of histone acetylation in the regulation of gene expression, treatment with JQ1 or the HDAC inhibitor mocetinostat was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 31 publications
(44 reference statements)
1
67
0
Order By: Relevance
“…We therefore evaluated whether our HAT inactivation signature was inversely associated with mocetinostat treatment, as such a relationship would support further exploration of the HAT inactivation signature as a candidate biomarker for identifying likely responders to this treatment. In an analysis of gene expression profiles of MDA-MB-231 breast cancer cells treated with mocetinostat (26), we found that HAT inactivation scores decrease following treatment (Fig. 5D; P = 0.053), consistent with mocetinostat counteracting the effects of lost p300/CBP HAT activity.…”
Section: Resultsmentioning
confidence: 56%
“…We therefore evaluated whether our HAT inactivation signature was inversely associated with mocetinostat treatment, as such a relationship would support further exploration of the HAT inactivation signature as a candidate biomarker for identifying likely responders to this treatment. In an analysis of gene expression profiles of MDA-MB-231 breast cancer cells treated with mocetinostat (26), we found that HAT inactivation scores decrease following treatment (Fig. 5D; P = 0.053), consistent with mocetinostat counteracting the effects of lost p300/CBP HAT activity.…”
Section: Resultsmentioning
confidence: 56%
“…In the majority of the studies, co-treatment of an HDAC inhibitor with another compound induced the inhibition of tumor growth and showed anti-proliferative effects (46,47,77,84,115,123,138,154). Also, several HDAC inhibitors are assosiated not only with autophagic cell death, but also apoptosis (44,55,70,71,84,97,153). Interestingly, many studies have found that HDAC inhibitors have the ability to convert ER-negative tumors to ER-positive tumors (111,160,161).…”
Section: Resultsmentioning
confidence: 99%
“…In other words, USP17 enzymes attenuated the Ras/MAPK pathway and cell viability was suppressed. On the other hand siRNA-mediated depletion of USP17, decreased the cytoxicity, indicating that the Ras/MAPK signaling pathway is involved in the synergistic effect of the combinational treatment (97). All these data show that the combination of HDAC and BET inhibitors could be used as potential therapeutic strategy for BC, given that it reduces the viability of TNBC cells, through induction of USP17.…”
Section: Hdac Inhibitors As Anti-cancer Agentsmentioning
confidence: 85%
See 2 more Smart Citations